Estudo de processos alternativos para a degradação de compostos de relevância ambiental com monitoramento dos produtos formados por espectometria de massas com fonte de ionização electrospray (ESI-MS) - Renata Pereira Lopes (2008)
Over the last decades, the growth of population and industrial activities has contributed to the aggravation of environmental problems, especially the contamination of superficial and underground waters. This is mainly caused by the enormous amounts of domestic or industrial wastes that are many times discarded directly into these bodies with no previous treatment. As conventional treatments have shown to be ineffective in removing a number of organic pollutants from water, this work aimed to evaluate the efficiency of alternative processes in promoting the degradation of prototype contaminants. Hence, the degradation of two insecticides (Thiametoxam and Imidacloprid) by two distinct processes (biodegradation by filamentous fungus and reductive degradation by zero-valent metals) in aqueous medium has been evaluated. Optimized results, as achieved via high performance liquid chromatography (HPLC) monitoring, indicated that the biodegradation of Thiametoxam and Imidacloprid by the fungi Paecilomyces lilacinus reached yields of 80% and 30%, respectively, after an incubation time of 15 days. Similarly, zero-valent tin, zinc, and magnesium were able to destroy both insecticides with degradation yields higher than 70%. Factorial designs were also employed to evaluate the influence of major parameters, i. e. reaction time, mass of the metal, and ultrasonic irradiation, on the reductive degradation of both insecticides. It was observed thatthe mass of the metal and the time of exposition to the ultrasonic irradiation significantly affected the degradation rates. It was also clear that the effect of ultrasonic radiation was more significant when smaller masses of the metal were used. Studies on the reductive degradation of the dye Indigo Carmine in aqueous solution were also performed. When treated with the zero-valent metals (Mg, Sn, Zn) in acidic medium (pH = 2), the dye was quickly degraded as visualized by the continuous solution discoloration. By bubbling atmospheric air into this discolored solution, however, the initial color was restored. This result, as achieved by a simple visual examination as well as by an UV-Visible spectroscopy monitoring, indicated that the dye is promptly and reversibly reduced by the zero-valent metalsyielding an unstable and colorless product. Upon treatment with atmospheric air, however, this reduced compound is promptly oxidized to restore the original dye. Electrospray ionization mass spectrometry (ESI-MS) was employed herein to monitor these egradation processes. In all cases, a number of degradation products could be detected and characterized thus demonstrating that this technique can be efficiently employed to monitor analogous environmentallyrelevantreactions that take place in water solution.